Suppose we want to factorise,

  2 x y + 3 x + 2y + 3

 

We note that,

   2xy & 2y both have 2

And

  3x & 3 both have 3

 

So, we put them together

 

  (2xy + 2y) + (3๐‘ฅ + 3)

2.jpg

 

So,

  2๐‘ฅy + 3๐‘ฅ + 2y + 3 = (๐‘ฅ + 1) (2y + 3)

 

Factorise 4ab − 5a − 12b + 15

3.jpg

  1. Chapter 14 Class 8 Factorisation
  2. Concept wise

Transcript

(2๐‘ฅy + 2y) + (3๐‘ฅ + 3) Both have 2 & y as common factor Both have 2 & y as common factor = 2y (๐‘ฅ + 1) + 3 (๐‘ฅ + 1) Now, (๐‘ฅ + 1) is common between them both = (๐‘ฅ + 1) (2y + 3) So, 2๐‘ฅy + 3๐‘ฅ + 2y + 3 = (๐‘ฅ + 1) (2y + 3) Factorise 4ab โˆ’ 5a + 12b + 15 4ab โˆ’ 5a + 12b + 15 = (4ab โˆ’ 12b) + (15 โˆ’ 5a) Both have 4 & b as common factor Both have 3 as common factor = 4b (a โˆ’ 3) + 5 (3 โˆ’ a) Writing (3 โˆ’ a) = โˆ’(a โˆ’ 3) = 4b (a โˆ’ 3) โˆ’ 5 (a โˆ’ 3) Taking (a โˆ’ 3) common = (a โˆ’ 3) (4b โˆ’ 5)

About the Author

Davneet Singh's photo - Teacher, Computer Engineer, Marketer
Davneet Singh
Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.